FERMENTASI PADAT DARI BEBERAPA LIMBAH LIGNOSELULOSA - Tjutju Nurhayati Syahri; Sri Komarayati; Gusailina Gusailina (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Lignocellulosic wastes such as rubber wood saw dust, bagasse, cayuput oil waste, municipal solid waste, vegetable waste were digested by solid state fermentation at Thermophillic temperature (55°C), and dry matter condition of 20-40Percent in 25 liter anaerobic fermentors.All of the lignocellulosic wastes, except for cayuput oil waste can be digested. The result revealed that the biogas productivity is about 1.66.5 V/V.r.d, methane content about 48.853.3 percent, retention time about 1334 days and efficiency of conversion about 12-61 percent.Solid state fermentation at the above mentioned conditions increases the biogas productivity of about 2-6 times more than that of the conventional method.Solid state fermentation of a mixture of rubber wood saw dust and water hyacinth (ratio 90/10) revealed that bioga» productivity was the lowest, retention time appeared to be the longest and the efficiency of conversion was relatively low (15%),, On the other hand, solid state fermentation of fresh municipal solid waste gave the highest productivity of about 6.5 V/V,r,d, relatively short retention time (16.6 days) and high efficiency of about 57%. Solid state fermentation of mixture of rice straw and water hyacinth (95/5) and also of the municipal solid waste, rubber wood saw dust, bagasse and water hya- cinth (68/ 15/ 1214) gave a high productivity and efficiency.